Students' Digital Competency Profile: An Observational Study of Five Areas of Digital Competency - Nuri Nuri; Putut Marwoto; Bambang Subali; Sulhadi Sulhadi; Rizal Agri Wahyuadi; Arini Ismiati (Borneo Research and Education Center, 2026)
This study is a preliminary investigation aimed at mapping the profiles and dynamics of students’ digital competencies based on the five domains of the Digital Competence Framework (DigComp): Information & Data Literacy, Communication & Collaboration, Digital Content Creation, Security & Safety, and Educational Problem Solving. This study employs a quantitative descriptive approach using an observational method involving 195 high school students selected through purposive sampling via the Google Forms platform, as well as 66 university students from 12 public and private universities. The research instrument consists of a Likert-scale-based observation sheet validated using the Rasch Model (Rating Scale Model) with the assistance of Winsteps software. Overall, students’ digital competencies fall into the “fairly good” category. The Security & Safety and Communication & Collaboration dimensions showed the highest levels of achievement, while Digital Content Creation ranked the lowest. The pattern of digital competency development shows an upward trend in higher grade levels, although not in a linear fashion. These findings indicate that students are still predominantly technology users and have not yet reached their full potential as digital creators. Therefore, there is a need to strengthen project-based learning and pedagogical innovations closely linked to digital skills to develop digital competencies more comprehensively and sustainably as part of efforts to support the 21st-century Global SDGs program.